Pengembangan Eksipien tablet dari Pati Termodifikasi - Feni Muhaimin Febriyanti; Ratih Aryani; Bertha Rusdi (UNISBA Press, 2024)
Abstract. Starch is a primary metabolite, namely polysaccharides derived from plants found in plant parts such as roots, stems, seeds, and fruits, this starch is composed of two molecular components, namely amylose and amylopectin. Modified starch is natural starch that has undergone advanced stages as an effort to change physical and chemical properties in a controlled manner so as to change one or more properties of the starch, so as to support the use of starch as an excipient in the pharmaceutical industry. This study was conducted to determine the potential of modified starch that can be used as an excipient in tablet preparations. The research conducted was a literature study using research articles available online. Based on the studies that have been carried out, modified starch has the potential as an excipient material in tablet making by covering fillers, crushers, and binders which is proven that modified starch can be selected as an excipient in the manufacture of tablet pharmaceutical preparations because modified starch has physicochemical properties that are more supportive than natural starch which has disadvantages if used as an excipient material in tablet preparation when used in its natural form. Abstrak. Pati merupakan metabolit primer yaitu polisakarida yang berasal dari tumbuhan yang terdapat pada bagian tumbuhan seperti pada akar, batang, biji, dan buah, pati ini tersusun dari dua komponen molekul yaitu amilosa dan amilopektin. Pati modifikasi adalah pati alami yang telah mengalami tahap lanjutan sebagai upaya perubahan sifat fisika dan kimia secara terkendali sehingga dapat merubah satu atau lebih sifat dari pati tersebut, sehingga dapat menunjang penggunaan pati sebagai bahan eksipien pada industri farmasi. Penelitian ini dilakukan untuk mengetahui potensi pati termodifikasi yang dapat digunakan sebagai bahan eksipien pada sediaan tablet. Penelitian yang dilakukan adalah studi literatur dengan menggunakan artikel penelitian yang tersedia secara online. Berdasarkan kajian yang telah dilakukan, pati termodifikasi mempunyai potensi sebagai bahan eksipien pada pembuatan tablet dengan meliputi pengisi, penghancur, dan pengikat yang dibuktikan bahwa pati termodifikasi dapat dipilih sebagai eksipien dalam pembuatan sediaan farmasi tablet karena pati termodifikasi memiliki sifat fisikokimia yang lebih menunjang dibandingkan dengan pati alami yang memiliki kekurangan jika dijadikan sebagai bahan eksipien pada pembuatan sediaan tablet apabila dipakai dalam bentuk alaminya.